Blockchain Technology for Secure and Transparent Supply Chain Management - Weller, Frank (International Journal of Computing and Engineering, 2024)
Purpose: The general objective of the study was to explore blockchain technology for secure and transparent supply chain management. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to blockchain technology for secure and transparent supply chain management. Preliminary empirical review revealed that blockchain technology had the potential to transform supply chain management by enhancing security and transparency. It emphasized the benefits of decentralization, immutability, and real-time visibility, which could reduce fraud and improve traceability. However, the study also highlighted challenges such as scalability, interoperability, and regulatory hurdles, which needed to be addressed for widespread adoption. Ultimately, the study suggested that companies investing in blockchain could gain a competitive advantage through increased efficiency and consumer trust, positioning blockchain as a crucial future component in supply chain management. Unique Contribution to Theory, Practice and Policy: Transaction Cost Theory, Social Exchange Theory and Resource-Based View (RBV) Theory may be used to anchor future studies on blockchain technology. The study made significant contributions to theory, practice, and policy. It integrated blockchain into existing supply chain theories, highlighting its role in reducing transaction costs and fostering trust. Practically, it recommended businesses invest in blockchain for enhanced transparency and efficiency, and leverage smart contracts to automate processes. It emphasized the need for supportive regulatory frameworks and addressed legal and ethical implications. The study advised a phased implementation approach and stakeholder collaboration, and suggested future research explore blockchain's long-term impacts and integration with IoT and AI. It underscored the broader implications for global trade and economic development.